2013
DOI: 10.5603/cj.a2017.0068
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of growth differentiation factor-15 in Chinese patients with heart failure: A prospective observational study

Abstract: Plasma GDF-15 is an independent predictor of all-cause mortality in Chinese patients with HF. It may potentially be used to stratify and prognosticate HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In chronic HFrEF, GDF‐15 served as a significant predictor for all‐cause mortality (Table ) even after multivariable adjustment for demographic factors and established biomarkers as hs‐TnT and Nt‐proBNP . GDF‐15 was shown to independently predict death or first HF rehospitalization in both HF subtypes even after adjusting for important clinical predictors including hs‐TnT and Nt‐proBNP .…”
Section: Next‐generation Biomarkers Under Researchmentioning
confidence: 98%
“…In chronic HFrEF, GDF‐15 served as a significant predictor for all‐cause mortality (Table ) even after multivariable adjustment for demographic factors and established biomarkers as hs‐TnT and Nt‐proBNP . GDF‐15 was shown to independently predict death or first HF rehospitalization in both HF subtypes even after adjusting for important clinical predictors including hs‐TnT and Nt‐proBNP .…”
Section: Next‐generation Biomarkers Under Researchmentioning
confidence: 98%
“…Currently, cardiac ultrasound (CUS) [5,15,16] and CMRI [5,17] are the major tools for the evaluation of ventricular remodeling and myocardial fibrosis at the international level. Above that, some biological indicators can also reflect the progress of fibrosis, such as ST2 and galectin-3 [5,[18][19][20]. In this trial, patients who have AMI and who receive PCI within 10 days will be the subjects, and the evaluation methods will include CUS; the T1 mapping sequence, cine sequence, and late gadolinium enhancement (LGE) sequence of CMRI; and measurements of biological indicators that reflect the progress of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies also observed a higher circulating concentration of GDF-15 in patients with CHF compared with healthy individuals (9)(10)(11). Moreover, certain studies in patients with CHF revealed that GDF-15 level was positively correlated and the disease severity, indicating that GDF-15 might act as a novel prognostic biomarker of CHF in risk stratification and prediction of adverse outcomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%